Reterritorializando o Ensino de História Indígena a Partir da Perspectiva de Tempo e História do Povo Javaé - Manrique, Tâmara Neiva Costa (2024)
The dissertation "Reterritorializing the Teaching of Indigenous History from the Perspective of Time and History of the Javaé People" addresses the epistemologies of the Javaé Indigenous people, who inhabit the Araguaia-Tocantins ethnoregion on Bananal Island, Tocantins. The objective is to examine how this community understands transformations in time and space, in contrast to the linear conceptions of Western history. The research adopts methodologies centered on the narratives developed by Indigenous teachers in the Extracurricular Projects of the Javaé Committee, linked to the Intercultural Indigenous Teaching Degree Program at the Federal University of Goiás (UFG). The theoretical frameworks include decolonial studies and the principles of transdisciplinarity and critical interculturality that underpin the Pedagogical Project of the Takinahakỹ Center for Indigenous Higher Education (UFG). As a product of the research, a didactic guidance material was created in the form of a website (link: www.tempoehistoriajavae.com), aimed at teachers in Basic Education, focusing on pedagogical practices based on the New Indigenous History and Decoloniality, with an emphasis on the Javaé perspective of time and history, contributing to the inclusion of Indigenous knowledge in history classes. The work highlights Indigenous intellectual leadership and the importance of integrating their epistemologies into the teaching of history, promoting dialogue between teachers from different epistemic contexts, especially between those in non-Indigenous basic education and the research produced by Indigenous teachers